2018
DOI: 10.1159/000487603
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Concept of Amino Acid Supplementation to Improve the Growth of Young Malnourished Male Rats

Abstract: Backgrounds/Aims: This study was aimed at understanding the relationship between plasma amino acids and protein malnutrition and at determining whether amino acid supplementation associated with malnutrition and growth improves linear growth in growing rats. Methods: Body length and plasma amino acids were measured in young male rats that were fed the following diet for 3 weeks, mimicking a low and imbalanced protein diets based on maize, a major staple consumed in developing countries: a 70% calorically restr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
1
5
0
1
Order By: Relevance
“…The amino acids of soy protein and casein in the present study are not completely similar to the previous study because of the difference in the purity and source of soy protein, but the ratio of the amino acids remained the same and the methionine and cystine were found to be the limiting amino acids in soy protein ( 22 ). A previous study confirmed that supplementary soy protein significantly improved the essential plasma amino acid concentrations in growth stunted rats which is evidenced in the present study ( 21 ). Although casein was higher than soy protein in AAS, soy protein improved the stunted growth better than casein.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The amino acids of soy protein and casein in the present study are not completely similar to the previous study because of the difference in the purity and source of soy protein, but the ratio of the amino acids remained the same and the methionine and cystine were found to be the limiting amino acids in soy protein ( 22 ). A previous study confirmed that supplementary soy protein significantly improved the essential plasma amino acid concentrations in growth stunted rats which is evidenced in the present study ( 21 ). Although casein was higher than soy protein in AAS, soy protein improved the stunted growth better than casein.…”
Section: Discussionsupporting
confidence: 92%
“…In poor areas, deficiency of protein intake is one reason for the stunted growth. Therefore, high quality and efficient protein consumption were important to improve the linear growth of children in the developing countries ( 21 ). The amino acids of soy protein and casein in the present study are not completely similar to the previous study because of the difference in the purity and source of soy protein, but the ratio of the amino acids remained the same and the methionine and cystine were found to be the limiting amino acids in soy protein ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…An article published in The Lancet in 1933 and redistributed by The Bulletin of the WHO in 2003 stipulated that the origin of Kwashiorkor syndrome, characterized by bilateral edema in undernourished children, was the maize diet in Ghana, a corn-based diet [60]. The maize diet is a diet high in carbohydrate, low in protein (6.4%), fat (3.4%) and minerals [35,61]. The maize diet was developed and first studied in monkeys to induce undernutrition [62].…”
Section: Undernutrition Modelsmentioning
confidence: 99%
“…Studi-studi yang dilaksanakan di Peru menunjukan adanya kenaikan berat badan pada anak setelah diberikan tepung gandum yang telah difortifikasi dengan asam amino lisin 10 . Penelitian di Jepang melaporkan bahwa suplementasi lisin, triptofan, asam amino rantai cabang, metionin, dan fenilalanin memiliki hubungan signifikan dengan panjang badan tikus yang mengalami malnutrisi 12 .…”
Section: Pendahuluanunclassified